Stand Up!. - Whitman, Gordon (Berrett-Koehler Publishers, 2018)
Stand Up! How to Get Involved, Speak Out, and Win in a World on Fire A society that actively combats racism, treats climate change as a serious threat, and ensures that all people have a living wage and a decent life for themselves and their families is not a progressive pipe dream. Victories are being won every day, all over the country. But they didn't happen just by clicking "donate" on a website. Gordon Whitman says that fundamental change demands forming the kind of face-to-face relationships that have sustained every social movement in history. For two decades, Whitman has been working with PICO National Network to equip tens of thousands to fight racial discrimination and economic injustice. He brings that experience to this book, describing five kinds of conversations that enable people to create organizations that can successfully overcome the forces of oppression and reaction. The first conversation to have is with ourselves, to make sure we're clear about our purpose and in it for the long haul. Then we need to share the personal story of how we came to this point with others--there is no more powerful way to connect. They in turn will share their stories, and then we can have the third conversation, about becoming a team. This team reaches out to people they know to talk about their concerns and priorities, building a broad base of supporters. Then, with our base at our back, we can have that final conversation, directly confronting the powers that be. Of course, this isn't as simple as it sounds. Appropriately enough, Whitman uses stories, his own and others, to illustrate how best to handle these conversations and to show how they work together to build a movement. We can't just sit on the sidelines sharing angry social media posts or signing online petitions. We need to get directly involved, reach out, knock on doors, and bring our whole selves to the table if the changes our country so desperately need are ever going to come